Legal, political and institutional limitations of the functioning of the Treaty on the Non-Proliferation of Nuclear Weapons - Kivliņa, Tīna Karlīne (Riga Graduate School of Law, 2023)
The Bachelor thesis “Legal, political and institutional limitations of the functioning of the Treaty on the Non-Proliferation of Nuclear Weapons” provides an analysis of aspects that limit the functioning of the Treaty on the Non-Proliferation of Nuclear Weapons (NPT). The main problem is the insufficiently created mechanisms when the NPT was established, leading to its signatory members to not being compliant to the legal norms set out in the NPT. The aim of the research is to analyse obstacles in three aspects – legal, political and institutional – in order to understand what impact these obstacles cause to the functioning of NPT. The objectives of the research are by understanding the limiting factors create proposals on how these limitations can be eliminated. The results of the research are that a new institutional mechanism shall be created in order to efficiently safeguard the NPT.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::International law; Treaty on the Non-Proliferation of Nuclear Weapons; United Nations; International Atomic Energy Agency